A sense of urgency - Kotter, John P. (Boston Harvard Business Press, 2008)
Most organizational change initiatives fail spectacularly (at worst) or deliver lukewarm results (at best). In his international bestseller Leading Change, John Kotter revealed why change is so hard, and provided an actionable, eight-step process for implementing successful transformations. The book became the change bible for managers worldwide.
Keywords: Organizational change